Mechanical behaviour of carbon nanotube fibers spun from vertically aligned arrays - Sun, Gengzhi (2013)
Due to their unique structure, carbon nanotubes (CNTs) have excellent properties including high thermal conductivity, high current capacity, and superior mechanical and chemical properties, which make them excellent one-dimensional materials with potentially wide applications. In order to utilize these properties, nano-scale CNTs must be prepared into macro-scale assemblies. CNT fibers, notably the fibers spun from vertically aligned CNT arrays, have therefore attracted great attention in recent years. Although these fibers have the inherent potential of leveraging on the excellence of CNTs, the individual fiber’s properties strongly depend on their structures and morphologies. The strength of the best fibers is still much lower than the theoretical and experimental results from individual CNTs or small CNT bundles. Moreover, up to now, no attention has been paid to the influence of test condition, specifically strain rate effects on mechanical performances of CNT fibers.